Promising directions in the treatment of chronic heart failure: improving old or developing new ones? - V. V. Kalyuzhin; A. T. Teplyakov; I. D. Bespalova; E. V. Kalyuzhina; N. N. Terentyeva; E. V. Grakova; K. V. Kopeva; V. Yu. Usov; N. P. Garganeeva; O. A. Pavlenko; Yu. V. Gorelova; A. V. Teteneva (Бюллетень сибирской медицины, 2022)
Unprecedented advances of recent decades in clinical pharmacology, cardiac surgery, arrhythmology, and cardiac pacing have significantly improved the prognosis in patients with chronic heart failure (CHF). However, unfortunately, heart failure continues to be associated with high mortality. The solution to this problem consists in simultaneous comprehensive use in clinical practice of all relevant capabilities of continuously improving methods of heart failure treatment proven to be effective in randomized controlled trials (especially when confirmed by the results of studies in real clinical practice), on the one hand, and in development and implementation of innovative approaches to CHF treatment, on the other hand. This is especially relevant for CHF patients with mildly reduced and preserved left ventricular ejection fraction, as poor evidence base for the possibility of improving the prognosis in such patients cannot justify inaction and leaving them without hope of a clinical improvement in their condition. The lecture consistently covers the general principles of CHF treatment and a set of measures aimed at inotropic stimulation and unloading (neurohormonal, volumetric, hemodynamic, and immune) of the heart and outlines some promising areas of disease-modifying therapy.